2012
DOI: 10.3390/molecules17066769
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Optimized Ultrasonic-Assisted Extraction of Flavonoids from Sparganii Rhizoma and Evaluation of Their in Vitro Antioxidant Activities

Abstract: An efficient ultrasound-assisted extraction technique was employed to extract total flavonoids from Sparganii rhizoma. The optimum extraction conditions for the highest yield of total flavonoids were ethanol concentration 53.62%, ultrasonication time 29.41 min and ultrasound power 300 W, which were determined using response surface methodology. The extraction yields of the optimal ultrasound-assisted extraction were higher than using conventional extraction. The crude extract was then purified on a polyamide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 31 publications
3
41
0
3
Order By: Relevance
“…This result agreed that extraction time is an important variable in UAE of phenolic compounds from plant materials. A longer extraction time permits more contact time for the cavitation bubbles to rupture more plant cells, result in an increase of the TPC extracted (Wang et al, 2012). The result was in accordance with Han et al (2012) who reported the improvement of phenolic of Betel nut seed with time by using UAE method, respectively.…”
Section: Effect Of Uas Time On Tpcsupporting
confidence: 88%
“…This result agreed that extraction time is an important variable in UAE of phenolic compounds from plant materials. A longer extraction time permits more contact time for the cavitation bubbles to rupture more plant cells, result in an increase of the TPC extracted (Wang et al, 2012). The result was in accordance with Han et al (2012) who reported the improvement of phenolic of Betel nut seed with time by using UAE method, respectively.…”
Section: Effect Of Uas Time On Tpcsupporting
confidence: 88%
“…In several studies, different amounts of flavonoids have been found in alfalfa tissues, which indicated that it may be utilized as a potential natural antioxidant compound [9][10][11][12]. Alfalfa may be a promising resource for flavonoids in the future.…”
Section: Introductionmentioning
confidence: 99%
“…It was clear that the model fit well with the response variables, considering the model could explain the variability of the responses. The coefficient of multiple determination (R2) was 0.9887, proving that a high correlation was obtained [13].…”
Section: Resultsmentioning
confidence: 87%